(untitled) (European Journal of Multidisciplinary Studies, 2017)
The paper aims to show that the children with learning diabilities have a high level of unconstrained primitive reflexes and that their undeserved suffering also comes from the increased presence of instinctive reflexive movements. This qualitative study is conducted with 20 percent of the children with learning disabilities 6-10 years old,in the city of Vlora,Albania. Also their cognitive development is held “as hostage” by stumbling power of the reflexive movements for the creation of new nerve pathways and schemes. The study is represented by a rich references with contemporary information on the role of primitive neurological reflexes in utero, in the first years of life and the non-integration consequences within their biological time. The study primarily measured the primitive retained reflexes in children in the study. As an instrument for measuring primitive reflexes, the study used "home test" developed by Sally Goddard Blythe. Measurements were made in just eight primitive reflexes based on the work of Petter and Sally Goddard Blythe; Moro, Rooting, Sucking, ATNR, TLR, Handheld, Galant, and STNR. Data were collected from the measurements on the type and percentage of the retained primitive reflexes. It was proven that children with learning disorders have a high level of retained primitive reflexes compared to other children. The findings of this study lead to the need for scientific research to inhibit the primitive reflexes at a young age, but also when they are present beyond their biological age.